Circulating PGLYRP1 Levels as a Potential Biomarker for Coronary Artery Disease and Heart Failure. Issue 5 (May 2021) - Han, Yanxin; Hua, Sha; Chen, Yanjia; Yang, Wenbo; Zhao, Weilin; Huang, Fanyi; Qiu, Zeping; Yang, Chendie; Jiang, Jie; Su, Xiuxiu; Yang, Ke; Jin, Wei
Abstract : Abstract: Coronary artery disease (CAD) and associated comorbidities such as heart failure (HF) remain the leading cause of morbidity and mortality worldwide attributed to, at least partially, the lack of biomarkers for efficient disease diagnosis. Here, we evaluated the diagnostic potential of serum peptidoglycan recognition protein 1 (PGLYRP1), an important component of the innate immunity and inflammation system, for both CAD and HF. A machine-learning method (random forest) was used to evaluate the clinical utility of circulating PGLYRP1 for diagnosis of CAD and HF in a total of 370 individuals. Causal links of chronic serum PGLYRP1 elevation to both diseases were further explored in ApoE −/− mice. The serum levels of PGLYRP1 were significantly higher in individuals with either chronic CAD or acute coronary syndrome than those in those without coronary artery stenosis (the control group) and even more pronounced in CAD individuals with concomitant HF. Our random forest classifier revealed that this protein performed better than other recommended clinical indicators in distinguishing the CAD from the control individuals. In addition, this protein associates more with the biomarkers of HF including left ventricular ejection fraction than inflammation. Notably, our mice experiment indicated that long-term treatment with recombinant PGLYRP1 could significantly impair the cardiovascular system as reflected from both increased atherogenic lesions and reduced fractional shortening of the left ventricle. Our findings, therefore, supported the circulating levels of PGLYRP1 as a valuable biomarker for both CAD and HF.